Outlined based geometric morphometric analysis in describing shape variation in suckermouth armoured catfishes (Pterygoplichthys spp.): Basis for the development of automated species identification system - Jaranilla, Loren Grace F. (Animo Repository, 2014)
The scientific community is facing taxonomic crisis. With still a huge number of species yet to be discovered, there is a great challenge to classify Earth’s biodiversity. Computer-based automated species recognition has been suggested as a prospective technology to aid in the quick identification of species, especially taxa that form part of routine investigation. Most automated species recognition systems mainly used geometric morphometric-based techniques. The present study investigates whether suckermouth armoured catfishes (Pterygoplichthys spp.), locally known as janitor fish, can be differentiated based on the shape of its head, using outline based geometric morphometric analysis.The variation in shapes is further determined and described. Specifically, we look at Pterygoplichthys spp., being an invasive species in the Philippines, which may establish negative effects in the freshwater environments. A total of 150 closely connected points were made along the outline of the head using tpsDig 2. Relative warp scores generated were used for the analysis of shape variations. Relative warp analysis demonstrated variation in the outline of the head. The four significant relative warps jointly accounted for 87.34% and 80.51% of the variation in the dorsal view and lateral view, respectively. This suggests that shape could be a potential character for the differentiation of Pterygoplichthys species, which would serve as the basis for the development of an automated species identification system.